Female reproductive success in gynodioecious Thymus vulgaris: pollen versus nutrient limitation and pollinator foraging behaviour. (17th June 2014) - Arnan, Xavier; Escolà, Anna; Rodrigo, Anselm; Bosch, Jordi
<x xml:space="preserve">Abstract</x> Gynodioecy is a dimorphic breeding system in which female individuals coexist with hermaphroditic individuals in the same population. Females only contribute to the next generation via ovules, and many studies have shown that they are usually less attractive than hermaphrodites to pollinators. Several mechanisms have been proposed to explain how females manage to persist in populations despite these disadvantages. The 'resource reallocation hypothesis' (RRH) states that females channel resources not invested in pollen production and floral advertisement towards the production of more and/or larger seeds. We investigated pollination patterns and tested the RRH in a population of Thymus vulgaris. We measured flower display, flower size, nectar production, visitation rates, pollinator constancy and flower lifespan in the two morphs. In addition, we measured experimentally the effects of pollen and resource addition on female reproductive success (fruit set, seed set, seed weight) of the two morphs. Despite lower investment in floral advertisement, female individuals were no less attractive to pollinators than hermaphrodites on a per flower basis. Other measures of pollinator behaviour (number of flowers visited per plant, morph preference and morph constancy) also showed that pollinators did not discriminate against female flowers. In addition, stigma receptivity was longer in female flowers. Accordingly, and contrary to most studies on gynodioecious species, reproductive success of females was not pollen limited. Instead, seed production was pollen limited in hermaphrodites, suggesting low levels of cross‐pollination in hermaphrodites. Seed production was resource limited in hermaphrodites, but not in females, thus providing support for the RRH. © 2014 The Linnean Society of London, Botanical Journal of the Linnean Society, 2014, 175, 395–408.